2014
DOI: 10.4103/2152-7806.132572
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative magnetic resonance imaging versus standard neuronavigation for the neurosurgical treatment of glioblastoma: A randomized controlled trial

Abstract: Background:Although the added value of increasing extent of glioblastoma resection is still debated, multiple technologies can assist neurosurgeons in attempting to achieve this goal. Intraoperative magnetic resonance imaging (iMRI) might be helpful in this context, but to date only one randomized trial exists.Methods:We included 14 adults with a supratentorial tumor suspect for glioblastoma and an indication for gross total resection in this randomized controlled trial of which the interim analysis is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Because of the high rate of residual tumor found on intraoperative imaging, the authors [4,8] described repeat surgical resection as an effective way to decrease the residual tumor volume retained-an afforded benefit owing to real-time assessment with the patient under anesthesia. In contrast, a 2014 randomized control trial comparing standard neuronavigation versus iMRI for resection of glioblastoma showed no difference with respect to the extent of resection, clinical performance, or overall survival [11]. Despite this lack of observed difference, the authors maintained that iMRI is useful in the appropriate situation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because of the high rate of residual tumor found on intraoperative imaging, the authors [4,8] described repeat surgical resection as an effective way to decrease the residual tumor volume retained-an afforded benefit owing to real-time assessment with the patient under anesthesia. In contrast, a 2014 randomized control trial comparing standard neuronavigation versus iMRI for resection of glioblastoma showed no difference with respect to the extent of resection, clinical performance, or overall survival [11]. Despite this lack of observed difference, the authors maintained that iMRI is useful in the appropriate situation.…”
Section: Discussionmentioning
confidence: 96%
“…The use of intraoperative MRI (iMRI) technology is a well-described neurosurgical technique that can enhance the probability of complete tumor excision, with several reports suggesting promising results for selected intracranial procedures [4,8,11]. Although these real-time MRI scans are characterized by small imaging fields, the visualized portal can be adequate for tumor localization and assessing adequacy of tumor resection in select orthopaedic oncology procedures where surrounding anatomy cannot be relied on to guide surgical resection, such as in the context of distorted anatomic fields through prior serial operations or radiation [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent interim analysis of a small, randomized, controlled trial comparing iMRI with conventional neuronavigation-guided surgery for suspected supratentorial glioblastomas did not show any advantage with respect to extent of resection, clinical performance, or survival for iMRI. 35 However, this is contrasted by the only other randomized, controlled trial, which found a statistically improved extent of resection in the iMRI group but without endpoints assessing quality of life or length of survival. 36 Given the current evidence, there is no clear quality improvement obtained from the added expense of iMRI, but this is an area in which further investigation is needed.…”
Section: Costly Innovations Without Clear Improvement In Outcomesmentioning
confidence: 88%
“…Further, no new data is presented (except the study by Wu et al, itself a conference proceeding which is hardly any robust evidence as of now, at least till the study is completed). Further, it is appropriate to point out that almost at the same time another prospective controlled trial for IOMR was published by Kubben et al [3]. This is actually a negative IOMR study.…”
mentioning
confidence: 94%